Utilization of Short-Form Videos (TikTok, Reels, Shorts) to Increase Brand Engagement and Visibility - Fatimah, Ade Fitria; Nasir, Mohamad (Journal of Digital Marketing and Search Engine Optimization, 2025)
The proliferation of social media has driven significant changes in digital marketing strategies, particularly through the utilization of short-form videos on platforms such as TikTok, Instagram Reels, and YouTube Shorts. Short-form videos are considered more effective in capturing the attention of modern audiences who prioritize speed of consumption and emotional engagement. This research aims to analyze how the use of short-form videos can increase brand engagement and visibility, as well as identify the key success factors of content on the three platforms. The research approach used is descriptive qualitative, with data collection techniques in the form of in-depth interviews with brand social media managers and observation of content performance on each platform. The results showed that content based on emotional storytelling, interactive elements, and the use of trending audio consistently increased engagement rates and brand visibility. TikTok showed the highest engagement rate, while Instagram Reels excelled in increasing visibility, and YouTube Shorts were effective in converting new followers. The success of the content is greatly influenced by understanding the characteristics of each platform's algorithm, authenticity of the narrative, and adapting to dynamic social trends. This study concludes that short-form content creation strategies need to integrate emotional, entertainment, informational, and algorithmic adaptation aspects to achieve maximum effectiveness. The practical implication of this research is the need for a cross-platform content approach that is adaptive and responsive to changes in digital audience behavior.